Continuous flow synthesis of mesoporous silica particles with tunable size and structure - Jundale, Rajashri B.; Prasad, Bhagavatula L. V.; Devi, R. Nandini; Kulkarni, Amol A. (Industrial and Engineering Chemistry Research, 2024)
We have developed a continuous process to prepare mesoporous silica particles of different sizes and narrow size distribution in a tubular reactor. The method is based on the use of well-known Stober synthesis in the presence of cationic surfactant in methanol-water solvent system and trimethylbenzene as pore swelling agent to form porous silica particles. We observed that reaction parameters had enormous effects on particle size, distribution, and numerous morphological aspects. We demonstrated that these properties may be modified by adjusting the reaction temperature, base concentration, and surfactant concentration. MSPs of spherical morphology with variable size from 400 to 1000 nm produced with the surface area >600 m(2)/g and pore diameter of 2-4 nm. Large scale production is demonstrated by increasing reactor volume using 1/4 in. PTFE tubing from 20 to 163 mL, with this production of MSPs increased from 0.35 to 3 g/h. The method has been extended for high yield production at the kilogram scale using this approach, which will pave the way toward the industrialization of mesoporous silica based materials.